THE ROLE OF SOME SECONDARY COMPOUND ON THE SUSCEPTIBILITY OF SOME PEAR VARIETIES TO INFECTION BY PEAR LACE BUG Stephanitis pyri (F.) (Tingidae: Hemiptera) - Nazar M. Al-Mallah (Mesopotamia Journal of Agriculture)
The results of the recent study showed the toxic effect of some secondary chemicals compounds extracted from pear leaves varieties such as (Zafarania, Othmani, Le-conte and Calleryana) in the pear lace bug Stephanitis pyri (F.); the results showed a variation in mortality percentage according to pear variety, concentration and insects stage. Phenols of the calleryana leaves showed a significant mortality percentage superior to the phenols of other pear varieties, which reached to 88, 71 % for nymph and adult at 10% concentration respectively. While the calleryana pear alkaloids demonstrated a significant mortality percentage superior to alkaloids of other varieties. It reached 80, 64% for nymph and adult at 10% concentration respectively. Similarly, calleryana pear terpens showed a significant mortality percentage superior to terpens of other varieties. It reached 63, 70% for nymph and adult at 10% concentration respectively; whereas the water-part of the calleryana pear leaves also showed. A significant mortality percentage reached 36, 42% for nymph and adult at 10% concentration respectively. Toxicity values have also confirmed that the calleryana pear phenols are more toxic, and its relative toxicity; followed by alkaloids, terpens and water-part respectively in comparision with other extracts of the rest varieties which had low relative toxicity to the Stephanitis pyri (F.).